The Effect of Environmental Uncertainty and Executive Characteristics on Tax Avoidance - Garten Huang, Lina; Trisnawati, Estralita (Dinasti Publisher, 2025)
The objectives of this study include: (1) To empirically test the effect of environmental uncertainty on tax avoidance; (2) To empirically test the effect of executive characteristics on tax avoidance; (3) To empirically test the role of company size moderating the effect of environmental uncertainty on tax avoidance; and (4) To empirically test the role of company size moderating the effect of executive characteristics on tax avoidance. The research uses an explanatory research design. The population of this study is public manufacturing in the food and beverage industry sector publishing its financial statements on the IDX in the 2018-2023 period. This research sampling method uses purposive sampling. This research data analysis technique uses Model Regression Analysis (MRA). From the results of data analysis it is concluded: (1) Environmental Uncertainty has an influence on tax avoidance. (2) Executive Characteristics affect tax avoidance. (3) Company size has no effect on tax avoidance. (4) Environmental uncertainty affects tax avoidance moderated by company size. (5) Executive characteristics have no effect on tax avoidance moderated by company size.